GAMBARAN PENJAGAAN ORAL HYGIENE PENGGUNA ORTODONTI CEKAT PADA MAHASISWA FKG UNIVERSITAS BAITURRAHMAH ANGKATAN 2017-2019 - Qurrata Akyuni Yusena; Kornialia Kornialia; Busman Busman (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: Patients with fixed orthodontic devices are at risk of oral hygiene problems. Dental students are considered to have adequate knowledge and should be able to use the right and proper way to maintain their oral hygiene when having fixed orthodontic appliances. The purpose of this study was to describe the methods used by students using fixed orthodontics at the Faculty of Dentistry, Baiturrahmah University Class of 2017-2019 in maintaining their oral hygiene. Methods: This is a descriptive study using a cross-sectional approach, the research sample was 53 students from the 2017-2019 class who used fixed orthodontic appliances by using a total sampling technique. Result: Almost all respondents declared that the use of fixed orthodontic appliances made food waste easier to adhere to (43.4% always experience it and 56.6% occasionally experience it). Almost all respondents had trouble cleaning their orthodontic appliance, (20.8% always experience it and 60.4% occasionally experience it). Most toothbrush they use for daily is conventional toothbrush (52.8 %). Other oral hygiene measures used daily by patients were dental floss (11.3%), interdental brush (20.8%), and mouthwash (13.2%). Most of the respondents clean their teeth after eat (60.4%). Few respondents use toothpicks where 9.4% always use them and 47.2% sometimes use them. Conclusion: This study concludes that the number of routine use of special orthodontic toothbrushes, dental floss, interdental brushes, and mouthwash is still low, and fixed orthodontic users who use toothpicks are still found.